Urban politics cities and suburbs in a Golden Age - Levine, Myron A. (Routledge, Taylor & Francis Group, 2020)
Urban Politics blends the most insightful classic and current political science and related literature with current issues in urban affairs. The book’s integrative theme is ‘power,’ demonstrating that the study of urban politics requires an analysist to look beyond the formal institutions and procedures of local government. The book also develops important subthemes: the impact of globalization; the dominance of economic development over competing local policy concerns; the continuing importance of race in the urban arena; local government activism versus the ‘limits’ imposed on local action by the American constitutional system and economic competition; and the impact of national and state government action on cities. Urban Politics engages students with pragmatic case studies and boxed material that use classic and current urban films and TV shows to illustrate particular aspects of urban politics. The book’s substantial concluding discussion of local policies for environmental sustainability and green cities also appeals to today’s students. Each chapter has been thoroughly rewritten to clearly relate the content to current events and academic literature.-- Back cover.